Neutralizing Antibody Kinetics and Immune Protection Against Herpes Simplex Virus 1 Genital Disease in Vaccinated Women. (24th February 2022) - Belshe, Robert B; Blevins, Tamara P; Yu, Yinyi; Nethington, Amanda E; Bellamy, Abbie; Bryant, Christopher; Morrison, Lynda A
Abstract: Background: Previously, our group conducted the Herpevac Trial for Women, a randomized efficacy field trial of type 2 glycoprotein D (gD2) herpes simplex virus (HSV) vaccine adjuvanted with ASO4 in 8323 women. Study participants were selected to be seronegative for HSV-1 and HSV-2. We found that the vaccine was 82% protective against culture-positive HSV-1 genital disease but offered no significant protection against HSV-2 genital disease. Efficacy against HSV-1 was associated with higher levels of antibody to gD2 at enzyme-linked immunosorbent assay (ELISA). Methods: To better understand the results of the efficacy study, we measured postvaccination concentrations of neutralizing antibody (nAb) to either HSV-1 and HSV-2 from HSV-infected study participants and matched uninfected controls. Statistical modeling was used to determine whether these responses were correlated with protection against HSV. Results: nAbs to either HSV-1 or HSV-2 were correlated with ELISA binding antibodies to gD2. HSV-1 or HSV-2 nAb findings support the observation of protection by higher levels of antibody against HSV-1 infection, but the lack of protection against HSV-2 remains unexplained. Conclusions: The protection against HSV-1 infection observed in the Herpevac Trial for Women was associated with nAbs directed against the virus, although the power to assess this was lower in the nAb study compared with the ELISA results owing to smaller sample size. Clinical trials registration: NCT00057330. Abstract : gD2 vaccine induced neutralizing antibody that was associated with protection against herpes simplex virus 1 (HSV) disease but did not protect against HSV 2 disease. Peak vaccine antibody was similar in titer to that stimulated by natural infection.